Genome‐Wide 5‐Methylcytosine and 5‐Hydroxymethylcytosine Signatures Analysis of Plasma Cell‐Free DNA in Schizophrenia - Gang Xue; Xia Wei; Li Li; Qi Zhang; Shanming Liu; Jun Zhang; Wen Hu; Qiannan Zhao; Wenjing Zhang; Chunyan Luo; Qiyong Gong; Bo Zhang; et al. (MedComm)
ABSTRACT Schizophrenia (SCZ) is a highly heritable neuropsychiatric disorder that affects ∼1% of people globally. Despite extensive research, there remains a lack of biomarkers for SCZ diagnosis and disease pathogenesis delineation. Cell‐free DNA (cfDNA), which carries the genetic and epigenetic signatures of origin tissue cells, may provide a noninvasive method for biomarker discovery. We performed cfDNA 5‐methylcytosine (5mC) and 5‐hydroxymethylcytosine (5hmC) sequencing of plasma samples from 66 individuals with SCZ and 77 healthy controls. We identified 954 differentially 5mC methylated regions (DMRs) and 1474 differentially 5hmC hydroxymethylated regions (DhMRs) that showed distinct patterns between SCZ and control samples. Many DMRs and DhMRs were associated with genes specifically expressed in brain tissues and were enriched in neuronal functions, as well as were enriched for genome‐wide association study (GWAS) of psychiatric and brain volume traits. Additionally, colocalization analysis revealed that DhMRs but not DMRs locations significantly overlapped with GWAS‐identified genomic loci of SCZ. Moreover, we observed associations between DMRs and DhMRs with brain regional measurements depicted by magnetic resonance imaging. Together, our findings indicated that cfDNA 5mC and 5hmC patterns are accessible epigenomic signatures that can serve as potential biomarkers and to help delineate SCZ pathogenesis.